SISTEM PENILAIAN KINERJA GURU PADA MI TARBIYATUS SHIBYAN MENGGUNAKAN BOOTSTRAP FRAMEWORK - Moh Muslikh; Retno Wardhani; Nur Nafiiyah (Universitas Islam Lamongan, 2017)
Teacher performance assessment system is a system that can help the problem of teacher assessment in the schools in in delivering the value of accurate and right on target, one of them is MI Tarbinyatus Shibyan Kemantren Paciran Lamongan which implement the performance appraisal of teachers to know the process of teaching is good and right for all student and for the promotion of teacher. Performance assessment of the teacher themselves were taken from the four criteria, namely Pedagogic, social, personality, there are four criteria of Professional the fourteen competencies. Thus is created the system of teacher performance assessment based on login step, the content of the data content of the teacher, the teacher's grades, report the results of the result value. Teacher performance assessment system is made as easy as possible, the system can be easily dioprasikan to assist the principal in the giving of value accurate and right on target.